Increased cardiorespiratory coordination in preeclampsia. (27th April 2017) - Berg, Karsten; Kraemer, Jan F; Riedl, Maik; Stepan, Holger; Kurths, Jürgen; Wessel, Niels
Abstract: Preeclampsia is one of the main sources of morbidity in pregnancy with a high mortality rate without a known ultimate cause. Using a corpus including 927 measurements of pregnant women with and without different hypertonic diseases at multiple stages of pregnancy, we utilised a new approach to analyse cardiorespiratory coordination. Since the recording quality of respiratory effort was limited due to a high signal to noise ratio, we applied an ECG derived respiration approach to create an ersatz respiratory signal. After applying the few available recordings with a sufficiently high quality of the respiratory signal to validate the substitute, coordigrams were calculated and quantified by utilising an epsilon method. We showed significant ( p   <  0.05) differences in the coordination in a matched (BMI, age, gestational week) comparison of preeclamptic and healthy subjects. Hopefully future applications of and improvements on these methods are able to create a fast and convenient prediction methodology to reduce the impact of this disease as well as help in the determination of its underlying cause.